A fast imaging method of scanning ion conductance microscopy. (November 2018) - Li, Gongxin; Fang, Xing
Highlights: A fast imaging method was proposed to improve the SICM imaging rate. The method contains compressive sampling strategy and a reconstruction algorithm. The method increases imaging rate for biological samples validated by experiments. The work is as a general method for fast and high-resolution imaging of STMs. Abstract: Scanning ion conductance microscopy (SICM) has attracted considerable attention in the biological field as a noninvasive, high-resolution and non-force contact imaging technology. However, the development of improvement to the SICM imaging rate remains a great challenge for applications of rapid or dynamic imaging. In this paper, a fast SICM imaging method is proposed to improve the imaging efficiency via the design of a compressive sampling strategy and a reduction in the reconstruction time of sparse signals using the 2D normalized iterative hard thresholding (2D-NIHT) algorithm. The imaging performance of the method is validated by the simulation of recovery of a random synthetic image, and the superiority of the 2D-NIHT algorithm is also demonstrated by comparison of its reconstruction performance with that of other typical algorithms. The actual imaging performance of the method in SICM is also validated by the imaging of two biological samples, a virus and a living cell, and the results show that the method can duplicate the sample surface topography with high-definition and shorter imaging time. Our study offers a general imaging method for the applications of scanning probe microscopies to realize faster and higher-resolution imaging of biological samples.